Health relevance of intestinal protein fermentation in young pigs. (30th August 2016) - Pieper, R.; Villodre Tudela, C.; Taciak, M.; Bindelle, J.; Pérez, J. F.; Zentek, J.
Abstract: The physiological role of the gastrointestinal microbiota has become an important subject of nutrition research in pigs in the past years, and the importance of intestinal microbial activity in the etiology of disease is doubtless. This review summarizes the recent knowledge related to the microbial ecology of protein fermentation and the appearance of protein-derived metabolites along the pig intestine. The amount of fermentable protein depends on factors such as dietary protein concentration, protein digestibility due to secondary or tertiary structure, the interaction with dietary compounds or anti-nutritional factors, and the secretion of endogenous proteins into the gut lumen. High protein diets increase the luminal concentrations and epithelial exposure to putatively toxic metabolites and increase the risk for post-weaning diarrhea, but the mechanisms are not yet clarified. Although the use of fermentable carbohydrates to reduce harmful protein-derived metabolites in pigs is well-established, recent studies suggest that the inclusion of fermentable carbohydrates into diets with low protein digestibility or high dietary protein level may not ameliorate all negative effects with regard to epithelial response. Based on the current knowledge, the use of diets with low levels of high-quality protein may help to reduce the risk for intestinal disease in young pigs.